Anxiety-associated factors among employees with different personality profiles: a cross-sectional study in China - Hao, Ran; Zuo, Jinfan; Jin, Haoyu; Wang, Yipeng; Zhang, Lei; Zhu, Yufang; Wang, Ye; Qi, Yixin; Qi, Jiale; Xia, Jing; Wu, Yibo; Hu, Jie (Frontiers in Psychology, 2023)
Introduction: Anxiety not only harms employees’ work efficiency and satisfaction but also presents as a hazard to their mental health. This study aimed to investigate the prevalence of anxiety among Chinese employees, identify their personality profiles and explore the anxiety-related factors in different personality profiles. Methods: This national investigation adopted the multistage random sampling method to recruit employees. A total of 3,875 employees were enrolled in this study, and 39.1% (1515/3875) of them were experiencing anxiety at the time of the study. Latent profile analysis (LPA) identified a three-profile solution among Chinese employees: average, resilient, and introverted. Results: Employees in the resilient profile had the lowest anxiety rate (16.1%, 132/822), and those in the average profile had the highest rate (46.8%, 1166/2494). Multivariate analysis results showed that for all personality profiles, self-efficacy was positively associated with anxiety, and work-family conflict was negatively associated with anxiety. High PSS and SE reduced the risk of anxiety and higher WFC and no partner increased the odds of anxiety in the average profile. For the introverted profile, female gender, and living in a city increased the chances of suffering from anxiety. Discussion: This study identified that each personality profile of Chinese employees had its own set of factors associated with anxiety, which could facilitate employers to provide targeted interventions to alleviate employees’ anxiety.